VAN LEEUWEN, Theo. Discourse and Practice : New Tools for Critical Discourse Analysis . New York: Oxford University Press , 172 páginas, 2008. - Dias, Tatiana Rosa Nogueira (Cadernos de Linguagem e Sociedade, 2011)
VAN LEEUWEN, Theo. Discourse and Practice : New Tools for Critical Discourse Analysis . New York: Oxford University Press , 172 páginas, 2008.